Evaluation of Emotion Recognition in Individuals With Autism Spectrum Disorder: Recommended Designs for Future Studies - Parisa Ghanouni; Laura Eves (Health Science Reports)
ABSTRACT Background and Aim Autism spectrum disorder (ASD) is a lifetime neurodevelopmental condition, which its prevalence is on the rise. Difficulties with emotion recognition and perspective‐taking are commonly observed in individuals with ASD, leading to a profound impact on their daily functions. The aim of this document was to offer a reflective perspective on the evolution of research in this area. Methods This document evaluates current research approaches. The analysis focused on identifying key trends, gaps, and areas for further investigations. Results Most studies that examined emotional face recognition in individuals with ASD yielded mixed findings regarding their ability in recognizing specific types of emotions. It may be considered that the heterogeneous population as well as the stimuli or experimental designs in previous studies play pivotal roles in inconsistencies in findings. Conclusion This commentary critically reflects on the previous studies, highlights trends in the current literature, and suggests how assessments can be implemented in future studies.